(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2025)
The study determined the relationship between staff development programmes and teachers task performance in public secondary schools in Awka education zone of Anambra State. Two research questions guided the study and two null hypothesis were tested at 0.05 level of significance. A correlational survey research design was adopted for the study. The population of the study consisted 1,258 teachers in the zone. A sample size of 126 teachers was drawn using proportionate stratified sampling technique. Two questionnaires titled: Staff Development Programme Questionnaire (SDPQ) and Teachers’ Task Performance Questionnaire (TTPQ) were used for data collection. The instruments were validated by three experts and subjected to internal consistency test using Cronbach alpha method which yielded 0.79 and 0.81 for SDPQ while that of TTPQ was 0.87. Data for the study were collected using direct administration and retrieval method. Pearson’s Product Moment Correlation was used to analyze data for the study. The findings revealed that there is a very high positive relationship between teachers’ attendance to conferences and their task performance in public secondary schools in Awka education zone of Anambra State, a very high positive relationship between teachers’ attendance to workshop and their task performance in public secondary schools in Awka Education Zone of Anambra State. Based on the findings, it was recommended among others that Principals should promote professional development programmes that focus on teachers’ subject matter knowledge and teaching skills which are effective in improving teacher task performance. This can include training in instructional strategies, curriculum development, assessment practices, and technology integration.